The Future of Education: How Mobile Learning, Microlearning, and Gamification are Revolutionizing Architecture Learning - Aryani Widyakusuma; Afriq Sarwarana Ramadhan Sudibyo (CV. Syntax Corporation Indonesia, 2024)
Human education has undergone various cycles of reform, yet many current education systems still rely on rigid models that do not meet the individual needs of students. Along with the advancement of technology and the digital revolution, there is a need for significant changes in the way education is delivered, especially in architectural education. This research aims to explore how mobile learning, microlearning, and gamification can revolutionize architecture education by meeting the increasingly diverse needs of students. This research uses a descriptive methodology that combines case studies and literature reviews to analyze current phenomena in architecture education. Findings show that the implementation of gamification, micro-learning, and mobile learning increases engagement, customization, and flexibility in architecture learning. Students now seek learning experiences that are interactive and customizable to their personal needs. By utilizing AI-based tools and more dynamic learning methods, educators can create learning environments that are more productive and responsive to the demands of the digital age. Architecture education in Indonesia, in particular, needs to adapt to international standards and modern challenges such as environmental sustainability. This research underscores the importance of integrating new technologies in architectural education to create more relevant and effective learning experiences. By adopting a more flexible and technology-driven approach, architecture education can better prepare students to face challenges in the world of work.